Improving Student’s Interest and Learning Outcome in Science about Single and Mixed Substances Applying Discovery Learning Assisted by ICT Media on Fifth Grade Students of SDN 2 Darmakradenan - Juriyah, Juriyah (Universitas Sebelas Maret, 2020)
This research aimed to find out the effect of applying Discovery Learning assisted by ICT media towards student’s interest and learning outcome in science about single and mixed substances of a total of 12 students on fifth grade of SDN 2 Darmakradenan. This classroom action research was conducted with a cyclical process consisted of 4 stages; plan, action, observation, and reflection, in 2 cycles. Based on the observation result of student’s interest, only 33,33% of pre-cycle showed their interest. Then, after first cycle , it improved 66,67%, and later improved to 91,67% at the end of second cycle. Based on the formative test result, only 41,67 of the pre-cycle passed the course. Then, it improved 75,00% in first cycle, and at the end of second cycle 100,00% passed the course. On the pre- cycle, the class’s average grade is about 55.56, and it improved to 83,33 after second cycle. Based on the analysis above, it can be concluded that Discovery Learning Assisted ICT Media can improve student’s interest and learning outcome on fifth grade students of SDN 2 Darmakradenan in science about single and mixed substances.